Strengthening Human Relations Among Students in The Field of Early Childhood Education with The Approach to Multicultural Education - Thaewthaisong, Tanaporn; Nueangpanom , Panida (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
The objectives of this research were to: 1. strengthen the human relations of first-year early childhood education students using a multicultural education approach, and 2. compare the human relations of these students before and after implementing the multicultural education approach. The sample consisted of 28 first-year early childhood education students enrolled in the second semester of the 2023 academic year at the Faculty of Education, Thepsatri Rajabhat University. The research instruments included: 1. a teaching and learning management plan (MCF 3) based on multicultural education guidelines for the course on organizing language and communication activities for early childhood, comprising 10 plans; and 2. a human relations assessment form with a 10-item, 50-point rating scale. The statistical methods used were mean, standard deviation, and t-test. The research results indicated that: 1) first-year early childhood education students who participated in activities designed to strengthen human relations through a multicultural education approach showed improved human relations; and 2) there was a statistically significant increase in human relations scores after the activities compared to before, with significance at the .05 level.